Assessment of volume segmentation in radiotherapy of adolescents; a treatment planning study by the Swedish Workgroup for Paediatric Radiotherapy. (January 2014) - Kristensen, Ingrid; Agrup, Måns; Bergström, Per; Engellau, Jacob; Haugen, Hedda; Martinsson, Ulla; Nilsson, Kristina; Taheri-Kadkhoda, Zahra; Lindh, Jack; Nilsson, Per
Abstract: Background and purpose. The variability in target delineation for similar cases between centres treating paediatric and adolescent patients, and the apparent differences in interpretation of radiotherapy guidelines in the treatment protocols encouraged us to perform a dummy-run study as a part of our quality assurance work. The aim was to identify and quantify differences in the segmentation of target volumes and organs at risk (OARs) and to analyse the treatment plans and dose distributions. Materials and methods. Four patient cases were selected: Wilm's tumour, Hodgkin's disease, rhabdomyosarcoma of the prostate and chordoma of the skull base. The five participating centres received the same patient-related material. They introduced the cases in their treatment planning system, delineated target volumes and OARs and created treatment plans. Dose-volume histograms were retrieved for relevant structures and volumes and dose metrics were derived and compared, e.g. target volumes and their concordance, dose homogeneity index (HI), treated and irradiated volumes, remaining volume at risk and relevant Vx and Dx values. Results. We found significant differences in target segmentation in the majority of the cases. The planning target volumes (PTVs) varied two- to four-fold and conformity indices were in the range of 0.3– 0.6. This resulted in large variations in dose distributions to OARs as well as in treated and irradiated volumes even though the treatment plans showed good conformity to the PTVs. Potential reasons for the differences in target delineation were analysed. Conclusion. Considerations of the growing child and difficulties in interpretation of the radiotherapy information in the treatment protocols were identified as reasons for the variation. As a result, clarified translated detailed radiotherapy guidelines for paediatric/adolescent patients have been recognised as a way to reduce this variation.